(untitled) (Faridpur Medical College Journal, 2017)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common hereditary enzyme disorder and more than 200 million people have a deficiency in this enzyme. G6PD deficiency is an X-linked enzyme defect, and one of its main signs is the presence of hemolytic anemia. It is a worldwide important cause of neonatal jaundice and causes life threatening hemolytic crisis in childhood. At later ages, certain drugs such as anti-malarial drugs and fava beans cause hemolysis among G6PD deficiency patients. The frequency and severity is influenced by genetic and cultural factors. It is common in Mediterranean, African and some East Asian populations but rare in Bangladeshi peoples. Genetic counseling may be of benefit for patients and their families. Other treatment is symptomatic and supportive. Faridpur Med. Coll. J. Jan 2017;12(1): 47-49